2009
DOI: 10.1371/journal.pone.0005593
|View full text |Cite
|
Sign up to set email alerts
|

The G428A Nonsense Mutation in FUT2 Provides Strong but Not Absolute Protection against Symptomatic GII.4 Norovirus Infection

Abstract: In November 2004, 116 individuals in an elderly nursing home in El Grao de Castellón, Spain were symptomatically infected with genogroup II.4 (GII.4) norovirus. The global attack rate was 54.2%. Genotyping of 34 symptomatic individuals regarding the FUT2 gene revealed that one patient was, surprisingly, a non-secretor, hence indicating secretor-independent infection. Lewis genotyping revealed that Lewis-positive and negative individuals were susceptible to symptomatic norovirus infection indicating that Lewis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
112
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 130 publications
(123 citation statements)
references
References 50 publications
7
112
1
1
Order By: Relevance
“…A seroprevalence study using donated blood also revealed that the presence of IgG titers against GII.4 strain was type A/B/O independent but correlated with the secretor phenotype (37). In another report, symptomatic GII.4 infections were also strongly associated with the Se phenotype (10). Although all the individuals in the current outbreak were Se ϩ , it is hard to conclude that GII.12 infection is Se ϩ dependent without Se-negative (Se Ϫ ) individuals exposed to these GII.12 strains.…”
Section: Discussionmentioning
confidence: 93%
“…A seroprevalence study using donated blood also revealed that the presence of IgG titers against GII.4 strain was type A/B/O independent but correlated with the secretor phenotype (37). In another report, symptomatic GII.4 infections were also strongly associated with the Se phenotype (10). Although all the individuals in the current outbreak were Se ϩ , it is hard to conclude that GII.12 infection is Se ϩ dependent without Se-negative (Se Ϫ ) individuals exposed to these GII.12 strains.…”
Section: Discussionmentioning
confidence: 93%
“…Evidence accumulated over the past 6 years indicates that HBGAs serve as ligands for NoV infection (5,6,15,17,18,25,26,39). However some studies showed discrepant results concerning the effect of either the ABO or the secretor phenotype, raising questions about the importance of HBGAs in norovirus infections (10,12,31,32,37).…”
Section: Discussionmentioning
confidence: 99%
“…In humans, the pleiotropic interaction of alleles at three loci, FUT3, FUT2, and ABO, determines the Lewis, secretor, and ABO phenotypes, respectively (28). The evidence that has accumulated from volunteers studies and from the analysis of outbreaks indicates that binding to these carbohydrates is required for infection (5,6,15,17,18,25,39). Moreover, various human NoV strains that bind to HBGAs present distinct specificities for HBGAs (13,14,38).…”
mentioning
confidence: 99%
“…Examples of infection in nonsecretors include ones due to norovirus GII.2 Snow Mountain (307), GII.4 (308,309), and GI.3 (310,311). In fact, combining the data from two GI.3 outbreaks, it can be calculated that 11 of 22 (50%) nonsecretors and 46 of 90 (51%) secretors were infected (310,311).…”
Section: Human Host Factors In Susceptibility and Resistance To Norovmentioning
confidence: 99%